2015
DOI: 10.1007/s00464-015-4157-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic mini-gastric bypass in patients age 60 and older

Abstract: LMGB can be safely performed with good weight loss in patients ≥60 years old, despite numerous comorbidities and previous abdominal operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Dr. Rutledge with 6,385 MGBs has had three operative deaths-the last in 2004. Peraglie found no deaths in his super-obese patients [23] and those age >60 [37].…”
Section: Discussionmentioning
confidence: 88%
“…Dr. Rutledge with 6,385 MGBs has had three operative deaths-the last in 2004. Peraglie found no deaths in his super-obese patients [23] and those age >60 [37].…”
Section: Discussionmentioning
confidence: 88%
“…Studies in which percentage total weight loss (%TWL) was reported in older people found loss of 17% to 38% after 1 to 6 years following gastric bypass and sleeve gastrectomy, and loss of 14% to 20% after adjustable gastric banding . For studies in which weight outcome was reported as percentage excess weight loss (%EWL), older persons undergoing RYGB or LSG lost 46% to 77% excess weight at 12 to 21 months, and 43% to 72% 2 to 6 years post‐operatively . After LAGB, studies reported %EWL of 14% to 36% at 1 year, and 35% to 48% at 5 years' follow‐up .…”
Section: Resultsmentioning
confidence: 99%
“…T2DM remission rates were mostly more than 84% [18,[20][21][22][23][26][27][28][29] Table 2 details the summary of complications in the same studies. 9 studies reported 0% mortality in their series.…”
Section: Efficacy-weight Loss and Resolution Of T2dmmentioning
confidence: 98%
“…Remaining studies were retrospective cohort studies, some comparing MGB to RYGB [20,24,28] while others Peraglie studied a specific subset of patients: the super super obese cohort [17] and in another study, those aged more than 60 years old [27].…”
Section: Efficacy-weight Loss and Resolution Of T2dmmentioning
confidence: 99%